Urgent Pneumonectomy as a Result of an Endoleak Type III—A Late Complication after Aortic Stent Implantation - Kirschbaum, Andreas; Mahnken, Andreas; Wallot, Pascal; Mirow, Nikolas (AORTA, 2022)
We report on an octogenarian, who was hospitalized with acute hemoptysis. Computed tomography angiography revealed a monstrously large thrombosed aortic aneurysm in the left thoracic cavity, completely displacing the lung. Eighteen years ago, the patient had suffered traumatic rupture of the descending aorta loco typico. Surgical exploration revealed a large calcified aneurysmal sac, which had perforated into the left lung. Pneumonectomy was performed, and hemoptysis did not reoccur.
Keywords: aortic stent; late complication; endoleak Type III; aortic aneurysm; pneumonectomy